Arbërisht Literature as an Example of Preserving a Cultural Identity Abroad - Katolo, Artur (Collectanea Philologica, 2023)
The purpose of this article is to demonstrate the origins of the literature of the Arbëreshë people and its impact on the survival of the language outside the country of origin. The cultural identity of the Italo-Albanians is marked by Byzantine inﬂuences: religion, economy, culture and military. The centuries-long, harsh Turkish occupation of Albania contributed to the cultural stagnation. Albanians in the territory of the Ottoman Empire were deprived of all rights, including the right to use their own language and profess their faith. The teaching of the Albanian language, as well as teaching in that language, and all publications were banned. Groups of Albanian refugees were welcomed in southern Italy as heroes and defenders of the faith. The few Albanian humanists were the descendants of immigrants educated in Ragusa, Padua or other Italian centres of research and education.